Intratumoral heterogeneity and immune modulation in lung adenocarcinoma in female smokers and never smokers - Trefzer, Timo; Schneider, Marc; Jechow, Katharina; Chua, Robert Lorenz; Muley, Thomas; Winter, Hauke; Kriegsmann, Mark; Meister, Michael; Eils, Roland; Conrad, Christian (Cancer research, 2022)
Lung cancer remains the leading cause of cancer-related death worldwide, despite declining smoking prevalence in industrialized countries. Although lung cancer is highly associated with smoking status, a significant proportion of lung cancer cases develop in patients who have never smoked, with an observable bias toward female never smokers. A better understanding of lung cancer heterogeneity and immune system involvement during tumor evolution and progression in never smokers is therefore highly needed. Here, we used single-nucleus transcriptomics of surgical lung adenocarcinoma (LUAD) and normal lung tissue samples from patients with or without a history of smoking. Immune cells as well as fibroblasts and endothelial cells responded to tobacco smoke exposure by inducing a highly inflammatory state in normal lung tissue. In LUAD, characterization of differentially expressed transcriptional programs in macrophages and cancer-associated fibroblasts provided insight into how the niche favors tumor progression. Within tumors, eight subpopulations of neoplastic cells were identified in female smokers and never smokers. Pseudotemporal ordering inferred a trajectory toward two differentiated tumor cell states implicated in cancer progression and invasiveness. A proliferating cell population sustaining tumor growth exhibited differential immune modulating signatures in both patient groups. Collectively, these results resolve cellular heterogeneity and immune interactions in LUAD, with a special emphasis on female never smokers.Single-cell analysis of healthy lung tissue and lung cancer reveals distinct tumor cell populations, including cells with differential immune modulating capacity between smokers and never smokers, which could guide future therapeutic strategies.